Acromiohumeral distance in subacromial impingement syndrome: A radiographic evaluation - Khanal, Krishna Raj; Rijal, Kiran Prasad; Pandey, Bimal Kumar; Pradhan, Rabindra Lal (Nepal Orthopaedic Association Journal, 2020)
INTRODUCTION: Subacromial impingement is one of the commonest causes of shoulder pain in Orthopaedic clinic. The etiology of subacromial impingement can be divided into intrinsic and extrinsic causes. There is still a controversy as whether the rotator cuff tendinitis is the result of impingement or vice versa. The knowledge about the dominant etiology would be beneficial for guiding the treatment. This study is intended to compare the acromiohumeral distance in plain radiograph (as one of the determinants of the extrinsic pathomechanism) in the shoulders with impingement and without impingement. It will help to determine whether the extrinsic or intrinsic mechanism is predominant factor of impingement in our population. METHODS: The acromiohumeral distance in the shoulder with subacromial impingement syndrome (n=35) and in those without impingement (n=38) were measured in plain radiograph and compared to know whether the narrowing of the subacromial space actually leads to rotator cuff impingement. RESULTS: The mean acromiohumeral distance in the patients with impingement was 7.43 ± 2.0 mm and the group without impingement was 8.10 ± 2.13mm. The p value for mean difference was 0.172. CONCLUSION: The mean acromiohumeral distance was lower in the patient with impingement than in patients without impingement. However this was not significant statistically.